2013
DOI: 10.1086/671345
|View full text |Cite
|
Sign up to set email alerts
|

Communication Channels and Word of Mouth: How the Medium Shapes the Message

Abstract: Consumers share word of mouth face to face, over social media, and through a host of other communication channels. But do these channels affect what people talk about and, if so, how? Laboratory experiments, as well as analysis of almost 20,000 everyday conversations, demonstrate that communicating via oral versus written communication affects the products and brands consumers discuss. Compared to oral communication, written communication leads people to mention more interesting products and brands. Further, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
252
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 293 publications
(268 citation statements)
references
References 39 publications
(39 reference statements)
14
252
0
2
Order By: Relevance
“…The characteristics of each conversation channel shape how, when, and what type of WOM is used (Berger and Iyengar 2013).…”
Section: The Concept Of Microblogging Word Of Mouth (Mwom): What It Imentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of each conversation channel shape how, when, and what type of WOM is used (Berger and Iyengar 2013).…”
Section: The Concept Of Microblogging Word Of Mouth (Mwom): What It Imentioning
confidence: 99%
“…Despite significant recent growth in the number and heterogeneity of WOM channels, we do not know enough about the way in which the characteristics of each conversation channel shape how, when, and what type of WOM is used and how it influences consumer decision making (Berger 2012;Berger and Iyengar 2013).…”
Section: Research Implicationsmentioning
confidence: 99%
“…Although not focused on science, past research has explored the psychological drivers of sharing content ranging from news articles to new products (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). We briefly summarize this work and use our data on scientists' discoveries to examine whether insights from other contexts also apply to the sharing of science.…”
Section: Content Effects: How Do Content Characteristics Affect Sharing?mentioning
confidence: 99%
“…First, people are more likely to share surprising, interesting, or otherwise entertaining content. Interesting products (e.g., night vision goggles) receive more online word of mouth than mundane products (e.g., soap) (12). Similarly, more interesting and surprising news articles are more likely to make the New York Times' most emailed list (4); more interesting and surprising urban legends are more likely to spread (6); and more interesting advertisements receive more views.…”
Section: Content Effects: How Do Content Characteristics Affect Sharing?mentioning
confidence: 99%
“…Recent studies have paid increasing attention to this topic, some of the main conclusions being that emotional response to product or service performance evokes WOM directly (Engel et al, 1969) and WOM spreading intention is correlated with the customer's perceptions of value and quality (Hartline and Jones, 1996). Berger and Iyengar (2013) have conducted laboratory experiments to find out how the medium shapes word-of-mouth and they concluded that written communication leads people to mention more interesting products and brands, but also gives them time to construct and refine what to write. Advertising can also generate WOM, if it shows uncertainty about the product, so it's vital to create advertisement high in conversational value (Buttle, 1998).…”
Section: Introductionmentioning
confidence: 99%